(3efGbH GdEeGe GdSfhSjs
(3ChdgG (B:s
(3bGd GdYdGeI SjOi CMeO aj Pjd GdOjHGL gh eMeO Hf jhSa Hf YeQ Hf TYjH GdSfhSj hHg YQa fSHg s
(3BNQgG (B:s
(3hSFd QVi Gddg Yfg Yf bhdg JYGdi(B: (3SGQYhG Edi eZaQI ef QHce Gg` LejYg ef WHbGJ GdEeGe SjOj YHOGdhgGH GdTYQGfj s
(3Vef eLehY , JQJjHgG (B: (3ef U (B334 - (3U(B340s
(3ZWi dUb HYV ChQGbgG Ydi hVhM GdceGJs
(3ef WHbGJ GdTYQGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B421 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs